Genetic variability and antimicrobial susceptibility profile of Mycoplasma gallisepticum and antimicrobial susceptibility profile of Mycoplasma synoviae isolated from various bird species in Peninsular Malaysia - Taiyari, Hossein; Abu, Jalila; Mohd Faiz, Nik; Zakaria, Zunita (Universiti Putra Malaysia, 2023)
Mycoplasma gallisepticum (MG) and M. synoviae (MS) can infect many bird species. Susceptible species of birds are responsible for spillover infections from poultry to wild birds. In Malaysia, previous studies reported the detection of MG in free-flying birds, but there is a lack of information on the characterization and antimicrobial susceptibility profile of these isolates. Therefore, this study aims to molecular characterize and assess the minimum inhibitory concentration (MIC) of MG and MS isolated from different bird species, including aviary, free-flying, and pet birds. Altogether 54 choanal slit swab samples were collected. All the swab samples were subjected to isolation and polymerase chain reaction (PCR) detection. Positive samples were subjected to molecular characterization and MIC assay. Molecular characterization was done using targeted gene sequencing, and microdilution MIC assay was employed to determine the antimicrobial susceptibility profile of the isolates. Using both culture and PCR techniques, 5.6% (3/54) of the samples were positive for MG, while MS was detected in 29.6% (16/54) and 40.7% (22/54) of samples using culture and PCR, respectively. The partial sequence of the mgc2 gene showed a distinct pattern of this gene in one of the MG isolates. Phylogenetic analysis of this isolate indicated that this isolate is a progeny of a Thailand poultry strain. Microdilution MIC assay indicated 100% resistance to erythromycin and chlortetracycline. The findings of this study indicate the possibility of avian interspecies transmission of MG and MS in Malaysia and the need for antimicrobial treatment dosage optimization.